Preference and Nutrition of Quail Breeder 16, Common Agricultural Feeds, and a Mix of Native Seeds as Northern Bobwhite Food - Jonathan A. Larson; Timothy E. Fulbright; Leonard A. Brennan; Fidel Hernandez; Fred C. Bryant (National Quail Symposium Proceedings, 2017)
Agricultural feeds are commonly dispersed along roads or in openings as an attractant or dietary supplement for northern bobwhites (Colinus virginianus). Quail Breeder 16e is a pelletized ration specifically developed by Lyssy & Eckel Feeds for breeding bobwhites to maximize nutritive content of diets. Captive bobwhites were used to examine relative preference of the pellets, sorghum, corn, soybean, and a mix of seeds of 8 native plant species. Protein, fat, acid detergent fiber, gross energy, and mineral content of the feeds were measured and we examined changes in body mass of bobwhites fed exclusive diets of each of the five feeds. A Latin rectangle experimental design with single and multiple-offer treatments was used to compare feed preference. Sorghum was most highly preferred in both the single and multiple offering experiments. Soybeans and the pelletized ration were least preferred. The native seed mix and corn were intermediate in preference. Nutritionally, soybeans had the highest protein (40%), highest fat (19%), and highest gross energy (21 kJ/g). Bobwhites fed exclusive diets of the native seed mix exhibited the greatest increase in body mass (40%), and birds fed the sorghum diet had the greatest decrease in body mass ( 8%). Providing supplements (pelletized rations and agricultural feeds) should not take precedence over managing bobwhite habitat to produce a variety of native grasses and forbs when improving bobwhite nutrition is a management objective.
Keywords: Colinus virginianus; Latin rectangle; northern bobwhite; nutrition; Quail Breeder 16e; relative preference; supplement